Wealth, Aristocracy and Royal Propaganda under the Hellenistic Kingdom of the Mithradatids in the Central Black Sea Region of Turkey - Erciyas, Deniz Burcu, (Colloquia Pontica ;, 2006)
A rebellious kingdom on the margins of the great Roman Empire or a kingdom in pursuit of a wider sovereignity? In spite of its notorious political history under the reign of Mithradates VI (120-63 BC), the social and economic history of the Black Sea region constitutes an uncharted territory. This book is a first comprehensive study of the archaeological, literary, and numismatic evidence from the central Black Sea region of Turkey during the Hellenistic Period. The monetary policies of the Pontic cities, testimonial to regional unification under Mithradates and his political influence on neighbouring lands are studied in separate sections. The section on the discovery of a remarkable tomb at Amisos reveals the emergence of the Pontic cities early as the fourth/early 3rd century BC.